ANALISIS TEGANGAN PENAMBAL DAN GAYA PAKU KELING PADA PEMASANGAN ANTENA ATC TRANSPONDER PESAWAT BOEING 737-200 - SUKAHIR (Politeknik Penerbangan Indonesia Curug, 2012)
ATC Transponder equipment consist of 2 (two) mains component. They are Transceiver and Antenna. The transceiver is installed on cockpit panels, while the antenna is installed on fuselage skin that located on upper body station 427. the doubler must be used before attached the antenna on fuselage skin. Base on SRM Boeing 737-200, the doubler geometry consists of 165.1 mm of length, 266.7 mm of width and the thickness is 2 mm. The doubler is attached on fuselage skin by 74 rivets, with 4.76 of diameter. The fuselage skin is representative ( modeled) by an existing skin with its geometry 354,33 mm of length, 266.7 mm of width and the thickness is 1.8 mm. Both materials of them are aluminum T2024-T3 with 72 GPa elastic modulus. The difference fuselage pressure is 53779 Pa with fuselage radius 1879.6 mm. So, the value of hoop tension stress is 56.05 MPa and longitudinal tension stress is 28.05 MPa. Because of them, the value of load can be counted, the result are 20284.5 N in X axis and 35803.5 N in Y axis. value of nett concentration factor (Ktn) of existing skin is 2.78 and the value of gross concentration factor (Ktg) is 3.8. The result of analysis are the maximum shear strength resultant of rivet is 675.76 N